Acute appendicitis presenting with MIS-C secondary to COVID-19 - Amanda Sturgill; Rachael Cannon; Shivani Patel; Andrea Horbey; Raymond Chua; Dilsa Souffrant; Stephanie Davenport (Elsevier, 2022)
Acute Appendicitis (AA) is among the most common causes of abdominal pain in children. Several physical exam findings, scoring systems, and imaging studies, such as ultrasonography and computed tomography, exist to assist clinicians in diagnosing acute appendicitis. Despite multiple tools for assessing suspected acute appendicitis, it remains a challenge to diagnose acute appendicitis in the pediatric population. A challenge that becomes increasingly more difficult if presenting with a comorbid condition. With the emergence of coronavirus disease 2019 (COVID-19) and subsequent discovery of multisystem inflammatory syndrome in children (MIS-C), this case series presents three pediatric cases of acute appendicitis presenting concurrently with MIS-C secondary to prior COVID-19 infection thus illustrating potential complications to diagnosing and managing acute appendicitis.